ANALISIS KUALITAS TEH DAUN KOPI ARABICA (Coffea arabica L.): PENGARUH LAMA PELAYUAN DAN LAMA PENGERINGAN - Ima, Meliani Suryati; Ahmadi, Kgs; Handayani, Sri (Jurnal Teknologi Pangan, 2025)
Coffee leaf tea is made from young shoots that inhibit the growth of coffee flowers and must therefore be removed. Coffee leaves contain antioxidant compounds such as flavonoids, alkaloids, saponins, caffeine, and polyphenols, which have the potential to provide health benefits. The objectives of this study were: (a) to analyze the effects of withering time and drying time on the physicochemical and organoleptic qualities of coffee leaf tea, and (b) to determine the best treatment combination. The research design used was a Completely Randomized Factorial Design (CRFD). Factor I was Withering Time (three levels: 1 hour, 2 hours, and 3 hours), and Factor II was Drying Time (three levels: 2 hours, 4 hours, and 6 hours). Each treatment combination was replicated three times. The results of the analysis of variance showed that the interaction between withering time and drying time had a highly significant effect on antioxidant activity, a significant effect on pH and sensory attributes (taste, aroma, and color), but no significant effect on moisture content and color parameters (L*, a*, b*). The best treatment was obtained with a withering time of 3 hours and a drying time of 4 hours, resulting in an antioxidant activity of 13.11%, moisture content of 2.58% (dry basis), pH of 6.06, brightness (L) of 22.72, redness (a) of -3.18, and yellowness (b*) of 6.23. Sensory scores were 2.75 for taste, 2.68 for aroma, and 2.80 for color.